Acidification potential of geological materials in a coal mining area in southern Brazil. (December 2022) - Albert, R.P.; Pinto, L.F.S.; Miguel, P.; Stumpf, L.; Leidemer, J.D.
Abstract: Acid mine drainage (AMD) is considered the major environmental hazard in coal mined areas. Characterizing the acidification potential of materials from representative geological drilling columns in coal pre-mined areas allows predicting the quality of a future constructed minesoil in post-mining areas. In this sense, acidification potential and neutralization potential quantifications enable selecting materials of the geological column that could be used to naturally neutralize acidifying materials and quantify alkaline materials for acidity correction. Therefore, this study aimed to estimate the probable composition of the constructed soil and its predisposition to cause acid mine drainage, and also estimating their potential to increase acidity in the soils and surface and subsurface waters of post-mining areas. The study was conducted in a coal mining area located in Southern Brazil. Geological material sampling included soil and rocks from six drill holes from the geological column representative of future coal mining areas. The mineralogical analysis was conducted using X-ray diffraction for the complete sample in powder form. The basic materials characterization was carried with chemical analyses: pH of water; pH of CaCl2 ; exchangeable cations; potential acidity. Results indicate the acidification general tendency in future constructed soils, and that control measures to prevent acid mine drainage generation must be adopted. In this regard, the use of BL and Coal (S2) seams is recommended, since they present an extremely high acidification potential. Furthermore, the controlled placement of sandstone layer with high potential acidity, and its treatment with carbonate materials addition is also recommended. Data regarding soil layers with high sum and base saturation, and the presence of smectite, typical of a Mollisol in F530 drill, reveal to environmental recovery teams the necessity of adapting to another soil condition. This condition must be chemically more fertile, but also physically harder to deal with than the Ultisol normally found in the current mining area. Highlights: Most countries in the world rely on coal for energy consumption. Candiota Mine has 750.68 ha affected by coal mining. Lithologies in mining areas predict the chemical behavior in future of soil profile. Acidification and neutralization potentials in the geological column predict acid mine drainage.